Low-Level Laser Therapy including Laser Acupuncture for Non-Specific Chronic Low Back Pain : Protocol for a Systematic Review - Hyewon Yeum; Dongwoo Nam (MEDrang Inc., 2019)
Background Low-level laser therapy (LLLT) including laser acupuncture (LA) has been widely used to treat chronic low back pain (CLBP), but there is no critically appraised evidence of the potential benefits. The purpose of this protocol for a systematic review was to enable the evaluation of the effectiveness of LLLT including LA for non-specific CLBP to identify the potential benefits. Methods The electronic databases MEDLINE (PubMed), Embase (Ovid), the Cochrane Central Register of Controlled Trials (CENTRAL), Korean medical databases (KoreaMed, KMBASE, KISS, NDSL, KISTI, OASIS), the Chinese database (CNKI), and Japanese databases (CiNII, J-STAGE) are recommended. Results Randomized controlled trials in LLLT including LA should be included in the searches. All data synthesis and subgroup analyses should be conducted using a Review Manager software. The Cochrane risk of bias tool can be used to evaluate methodological quality of the studies. A risk ratio or mean difference with a 95% confidence interval will show the effects of LLLT including LA. Conclusions The primary outcome would be pain intensity and functional status/disability due to low back pain. The secondary outcome would be a global measurement of recovery or improvement, quality of life and adverse event.